Recent advances in nanotechnology approaches for non-viral gene therapy. (12th October 2022) - Jiang, Yihang; Fan, Miaozhuang; Yang, Zhenxu; Liu, Xiaochen; Xu, Zhourui; Liu, Shikang; Feng, Gang; Tang, Shuo; Li, Zhengzheng; Zhang, Yibin; Chen, Shilin; Yang, Chengbin; et al.
Abstract : Gene therapy has shown great potential in treating many diseases by downregulating the expression of certain genes. Various functional non-viral vectors have been well designed to enable efficient gene therapy. Abstract : Gene therapy has shown great potential in the treatment of many diseases by downregulating the expression of certain genes. The development of gene vectors as a vehicle for gene therapy has greatly facilitated the widespread clinical application of nucleic acid materials (DNA, mRNA, siRNA, and miRNA). Currently, both viral and non-viral vectors are used as delivery systems of nucleic acid materials for gene therapy. However, viral vector-based gene therapy has several limitations, including immunogenicity and carcinogenesis caused by the exogenous viral vectors. To address these issues, non-viral nanocarrier-based gene therapy has been explored for superior performance with enhanced gene stability, high treatment efficiency, improved tumor-targeting, and better biocompatibility. In this review, we discuss various non-viral vector-mediated gene therapy approaches using multifunctional biodegradable or non-biodegradable nanocarriers, including polymer-based nanoparticles, lipid-based nanoparticles, carbon nanotubes, gold nanoparticles (AuNPs), quantum dots (QDs), silica nanoparticles, metal-based nanoparticles and two-dimensional nanocarriers. Various strategies to construct non-viral nanocarriers based on their delivery efficiency of targeted genes will be introduced. Subsequently, we discuss the cellular uptake pathways of non-viral nanocarriers. In addition, multifunctional gene therapy based on non-viral nanocarriers is summarized, in which the gene therapy can be combined with other treatments, such as photothermal therapy (PTT), photodynamic therapy (PDT), immunotherapy and chemotherapy. We also provide a comprehensive discussion of the biological toxicity and safety of non-viral vector-based gene therapy. Finally, the present limitations and challenges of non-viral nanocarriers for gene therapy in future clinical research are discussed, to promote wider clinical applications of non-viral vector-based gene therapy.